2002
DOI: 10.1111/j.1348-0421.2002.tb02701.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Investigation ofBartonella henselaeInfections in Clinically Cat‐Scratch Disease‐Suspected Patients, Patients with Cardiovascular Diseases, and Healthy Veterinary Students in Japan

Abstract: Seroprevalence of Bartonella henselae was investigated in Japan in 48 individuals clinically suspected of having cat‐scratch disease (CSD), 159 patients with cardiovascular diseases, and 129 healthy veterinary students. Of 48 CSD‐suspected patients examined, 19 (39.6%) were positive for B. henselae‐IgG and 4 (8.3%) for B. henselae‐IgM. Of 159 patients with cardiovascular diseases, 5 (3.1%) were positive for B. henselae‐IgG. In healthy veterinary students, 14 of 129 (10.9%) were positive for B. henselae‐IgG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
1
16
1
2
Order By: Relevance
“…The seroprevalence of B. henselae was 1.7% in veterinary-associated individuals. This prevalence was lower than in previous reports from Japan, which were 15% in veterinary professionals [20] and 10.9% in veterinary school students [17]. It was also lower than the 7.1% in the veterinary population that attended the veterinary Conference in Ohio, USA [30].…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…The seroprevalence of B. henselae was 1.7% in veterinary-associated individuals. This prevalence was lower than in previous reports from Japan, which were 15% in veterinary professionals [20] and 10.9% in veterinary school students [17]. It was also lower than the 7.1% in the veterinary population that attended the veterinary Conference in Ohio, USA [30].…”
Section: Discussioncontrasting
confidence: 49%
“…Furthermore, year of experience with cats was the only identified variable associated with seropositivity [30]. There were also two serological investigations in veterinary populations in Japan [17,20]. Kumasaka et al [20] reported that 15% (35/233) of veterinary professionals were seropositive for B. henselae, and young female veterinary assistants and animal beauticians were more likely to be infected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most cases are diagnosed based on clinical manifestations, the history of contacts with cats, serology (14,20,24,26,28,33) or PCR-based methods for examining the biopsy specimens (2, 10, 28). However, the isolation of the organism from patients is relatively difficult and only a few cases of the organism isolation have been reported worldwide (7,9,18,25), because suitable material is not available, the culture conditions are not appropriate or the organism shows fastidious, cytozoic and slow-growth properties.…”
mentioning
confidence: 99%